1996
DOI: 10.1029/95ja02760
|View full text |Cite
|
Sign up to set email alerts
|

Reinterpretation of the 6300‐Å airglow enhancements observed in ionosphere heating experiments based on analysis of Platteville, Colorado, data

Abstract: Airglow enhancement observations have been considered as supporting evidence of electron acceleration in ionosphere heating experiments by high‐power HF waves. Here we analyze some of the 6300‐Å airglow data from the Platteville, Colorado, heating experiments of 1970, employing new electron impact excitation rates for the O(1D) state and empirical, but in accord with experimental and theoretical constraints, plasma heating rates and show that these airglow enhancements should be attributed to excitation by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 46 publications
(30 reference statements)
4
53
0
1
Order By: Relevance
“…Stochastic interactions heat the bulk of electrons (e.g. Gurevich et al, 1985;Dimant et al, 1992;Mantas and Carlson, 1996;Gurevich and Milikh, 1997;Istomin and Leyser, 2003). Both effects are well documented (e.g.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Stochastic interactions heat the bulk of electrons (e.g. Gurevich et al, 1985;Dimant et al, 1992;Mantas and Carlson, 1996;Gurevich and Milikh, 1997;Istomin and Leyser, 2003). Both effects are well documented (e.g.…”
Section: Introductionmentioning
confidence: 89%
“…Mantas and Carlson, 1996;Mishin et al, 2004). It is very sensitive to the distribution of thermal electrons (TEDF), which may strongly deviate from a Maxwellian distribution (MD) due to inelastic collisions with molecular nitrogen N 2 (Mishin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Numerical simulations for ionospheric conditions have yielded power-law like tails of the electron distribution (Wang et al, 1997). Others (primarily Mantas, 1994;Mantas and Carlson, 1996) argued that the enhancements in 6300Å could well be explained by excitation of the high energy tail of the heated electron distribution and that the early observations of enhancements in 5577Å were scarce and unreliably close to the instrumental noise level.…”
Section: Latitudes Even So Little Is Known Aboutmentioning
confidence: 99%
“…Mantas and Carlson (1996) developed a quantitative model relating to the heating enhanced electron temperature to the 630.0 nm intensity and showed that the thermal electron excitation of the O( 1 D) state is enough to explain the emission intensity observed during the ionosphere heating experiments.…”
Section: High Energy Tail Of the Thermal Electronsmentioning
confidence: 99%
“…It has also been well known that powerful HF radio wave transmission leads to strong enhancement of the temperature of the ionospheric electrons. Mantas and Carlson (1996) developed a quantitative model relating to the heating enhanced electron temperature to the 630.0 nm intensity and argued that the thermal electron excitation of the O( 1 D) state is enough to explain the emission intensity observed during the ionosphere heating experiments. However, in an analysis of simultaneous observations of the electron density, temperature and the red line intensity, Sergienko et al (2000) showed that the model significantly overestimates the observed emission intensity.…”
Section: Introductionmentioning
confidence: 99%